Fontenelle : jouer et philosopher - Christophe Martin (Etudes Epistémè)
As Leibniz’s interlocutor, as an assiduous (and quietly polemic) reader of Pascal, and as a distant follower of Epicurus, Fontenelle had every reason not to ignore the moral and philosophical importance of gambling. In fact, Fontenelle’s thought meets the question of gambling in various ways. In a literal sense, Fontenelle approaches the game as an object of mathematical and philosophical reflection, in particular in his “Éloge de Montmort”, the latter having endeavored to apply modern arithmetic to the analysis of games of chance. While Fontenelle’s remarks may seem relatively peripheral in his work, the analysis he offers of “the spirit of the game” opens up key issues of his philosophical practice. Understood as a paradigm, gambling is indeed, for Fontenelle, the emblem of a philosophy that gives an essential role to playfulness and banter. It is also the paradigm of a certain idea of happiness that Fontenelle explicitly links to the practice of calculation in the game of chance: because “wisdom must always have the tokens in hand”. Finally, the Fontenellian conception of the universe as well as its cosmology allow us to discern the idea of a universal playfulness at work in nature, breaking with the providentialist conception of a great hidden agenda and an eternal order.